The Effect of Operating Cash Flow, Financial Cash Flow, and Debt Level on Stock Return with Company Size as a Moderating Variable - hesty nur aini yustina; Miladiah Kusumaningarti; Putri Awalina (LP2M IAIN Palopo, 2026)
This study aims to examine the effect of operating cash flow, financing cash flow, and debt level on stock returns, with company size as a moderating variable. The approach used is quantitative with a causal research design. The research data consists of secondary data sourced from annual financial reports and closing stock prices of transportation and logistics companies listed on the Indonesia Stock Exchange during the period 2022–2024. Sampling was conducted using purposive sampling, resulting in 60 observations. The data analysis techniques applied include multiple linear regression and Moderated Regression Analysis (MRA). The results show that, partially, operating cash flow, financing cash flow, and debt level do not have a significant effect on stock returns, although simultaneously, these three variables form a significant model. The moderation analysis shows that company size moderates the relationship between operating cash flow and stock returns in a negative direction, while no moderating effect was found for cash flow from financing activities and debt levels. These findings indicate that investors tend to pay more attention to company characteristics and general market perceptions than to short-term financial information when assessing potential stock returns